45 Polo-like-kinase-1 as a potential therapeutic target in merkel cell carcinoma. Issue 5 (May 2015) - Kadletz, L.; Heiduschka, G.; Lill, C.; Schneider, S.; Seemann, R.; Bigenzahn, J.; Thurnher, D.
<x xml:space="preserve">Abstract</x> Background Merkel cell carcinoma (MCC) is a rare and aggressive skin malignancy. Late stage MCC treatment options include radio- and chemotherapy. The aim of this study was to assess the expression of polo-like-kinase-1 (PLK1) in MCC and whether the PLK1 inhibitor BI2536 is a potential therapeutic option in MCC. Material and methods To evaluate PLK1 expression in patient specimens a tissue microarray was constructed for immunohistochemical staining. The two MCC cell lines MCC13 and MCC26 were exposed to increasing doses of BI2536 in combination with cisplatin or irradiation. Suppression of PLK1 was measured by Western blot analysis. Clonogenic assays were performed after irradiation to evaluate long-term results. Apoptotic and necrotic fractions were measured via flow cytometry. Results BI2536 is capable of inhibiting cell proliferation with an IC50 of 12nM. Combination with cisplatin is synergistic and a partially synergistic effect in combination with irradiation was detected. Clonogenic survival is inhibited synergistically. BI2536 induces apoptosis in MCC cell lines. Conclusion PLK1 seems to be a promising target in the treatment of MCC. Treatment with BI2536, a potent inhibitor of PLK1, resulted in suppression of MCC growth in vitro. Our data warrant further investigations for the potential use of BI2536 in MCC.